Sinusitis (2000)
¿Qué son los senos para nasales?/ ¿Qué es la sinusitis?/Tipos de sinusitis/Causas de sinusitis/Factores que predisponen/La sinusitis y su relación con otras enfermedades del tracto respiratorio/Signos y síntomas/Complicaciones de la sinusitis.